Morphometrical study of pedicles in lumbar vertebrae and its clinical significance. - Chandni G,; Poonam K,; Arvind KP,; Antony SD, (Department of Surgery, UKM Medical Centre, 2014)
With the recent increased use of various pedicle screw instrumentation, there is concern about injuries to the pedicle cortex, nerve root, facet joint and adjacent vital structures by discordant pedicle screw size. A pedicle screw is a bone screw inserted in to the pedicles of the vertebrae in patient‘s back bone for the purpose of immobilizations or fixations. Success depends upon accuracy of choice of screw & morphometry of the pedicle. Understanding the morphometry of pedicles may decrease the concerned risks. So, the present study was undertaken to obtain the width and height of the pedicles of 50 dry lumbar vertebrae. The lumbar vertebrae were divided into two groups typical (L1-4) and atypical (L5) depending on the atypical features of L5. Pedicles of lumbar vertebrae were measured using callipers. Statistical analysis was done and the mean and standard deviations for each side was calculated. The mean height, width on right and left side typical vertebrae was 13, 7 and 8, 12mm. The mean height, width on right and left side atypical vertebrae was 14, 14 and 13, 14 mm, respectively. There was significant correlation between height and width of right and left side of typical and atypical vertebrae as the value was <.01. This study may be a reference guide to the choice of the size of the pedicle screw for screw fixations.